Evropsko čezmejno sodelovanje v družinskih zadevah - Kramberger Škerl, Jerca (Podjetje in delo, 2021)
The need for cross-border cooperation in family matters in the European Union was already identified and politically expressed in the 1990s. The first legislative act adopted in this field was the Brussels II Regulation of 2000. It unified, on the EU level, the rules on international jurisdiction and the recognition and enforcement of judgments in matrimonial matters and parental responsibility. In 2021, six EU regulations are in use in this field. In 2022, the second recast of the Brussels II Regulation will enter into force. Besides the mentioned cross-border procedural rules, the regulations also introduce a unified choice of law rules, while other EU regulations in the field of private international law enable simplified cross-border service of documents and taking of evidence. The number of unified rules in cross-border family disputes is thus growing, which enhances legal certainty of European families. However, the fragmented regulation and different temporal and territorial scopes of application of the "family regulations" result in a complex mosaic of rules, which is often unclear and difficult to apply. The paper aims to present a comprehensive view of the legislation in force and provides information on the interplay among different regulations. Thus, it strives to effect a rapid and correct application of this legislation, which is of crucial importance for European citizens. The paper also emphasises the importance of the broader context of the EU cooperation in family matters, namely the EU private international law in general, and of the international treaties in family law, especially the Hague conventions.
Keywords: Brussels II bis Regulation; cross-border dispute; čezmejni spor; dedno pravo; družinsko pravo; EU law; family law; Maintenance Regulation; mednarodno zasebno pravo; pravo EU; private international law; property regimes regulations; Rome III Regulation; succession law; Succession Regulation; uredba Bruselj II bis; Uredba o dedovanju; Uredba o preživninah; uredba Rim III; uredbi o premoženjskih razmerjih